A recently isolated human commensal Escherichia coli ST10 clone member mediates enhanced thermotolerance and tetrathionate respiration on a P1 phage‐derived IncY plasmid. Issue 2 (12th October 2020) - Kamal, Shady Mansour; Cimdins‐Ahne, Annika; Lee, Changhan; Li, Fengyang; Martín‐Rodríguez, Alberto J.; Seferbekova, Zaira; Afasizhev, Robert; Wami, Haleluya Tesfaye; Katikaridis, Panagiotis; Meins, Lena; Lünsdorf, Heinrich; Dobrindt, Ulrich; et al.
Abstract: The ubiquitous human commensal Escherichia coli has been well investigated through its model representative E. coli K‐12. In this work, we initially characterized E. coli Fec10, a recently isolated human commensal strain of phylogroup A/sequence type ST10. Compared to E. coli K‐12, the 4.88 Mbp Fec10 genome is characterized by distinct single‐nucleotide polymorphisms and acquisition of genomic islands. In addition, E. coli Fec10 possesses a 155.86 kbp IncY plasmid, a composite element based on phage P1. pFec10 harbours multiple cargo genes such as coding for a tetrathionate reductase and its corresponding regulatory two‐component system. Among the cargo genes is also the Transmissible Locus of Protein Quality Control (TLPQC), which mediates tolerance to lethal temperatures in bacteria. The disaggregase ClpGGI of TLPQC constitutes a major determinant of the thermotolerance of E. coli Fec10. We confirmed stand‐alone disaggregation activity, but observed distinct biochemical characteristics of ClpGGI‐Fec10 compared to the nearly identical Pseudomonas aeruginosa ClpGGI‐SG17M. Furthermore, we noted a unique contribution of ClpGGI‐Fec10 to the exquisite thermotolerance of E. coli Fec10, suggesting functional differences between both disaggregases in vivo. Detection of thermotolerance in 10% of human commensal E. coli isolates hints to the successful establishment of food‐borne heat‐resistant strains in the human gut. Abstract : The ubiquitousness of commensal Escherichia coli in post‐industrial humans calls for the investigation of their physiological characteristics. Thermotolerance, unconventional anaerobic respiration, and detoxification cargo genes are encoded on an IncY derived plasmid harbored by a typical member of the common ST10 clone. Thermotolerance is well represented in commensal isolates with the key disaggregase ClpGGI to be exquisitely thermostable. Fire symbol by ya‐webdesign.com.